THE EFFECT OF PERCEIVED USEFULNESS AND EASE OF USE ON MSME ENTREPRENEURS' INTEREST IN USING THE CASHIER APPLICATION - Sugianarti, Sugianarti; Dwi Widiyastuti, Reni; Risal, Risal (Jurnal Akuntansi dan Keuangan (JAK), 2026)
The development of information technology has brought significant changes in business management, including the Micro, Small and Medium Enterprises (MSMEs) sector. To remain competitive, MSME entrepreneurs are expected to utilize technology that can increase efficiency and effectiveness, such as using cashier applications. This study aims to examine how perceived usefulness and perceived convenience influence interest in using cashier applications for recording sales transactions. The research employed a quantitative method with an explanatory approach, focusing on testing causal relationships between variables through inferential statistical analysis. Data were collected using questionnaires distributed to 100 MSME entrepreneurs in Pontianak City. Analysis included validity and reliability tests, classical assumption tests, and multiple linear regression to examine partial and simultaneous effects. Results indicate that perceived usefulness and perceived convenience both partially and simultaneously have a positive and significant effect on interest in using cashier applications, with perceived usefulness being the most dominant factor. These findings support the Technology Acceptance Model (TAM), which explains that technology adoption is influenced by users’ beliefs. The results provide important implications for developers and stakeholders in promoting MSME digitalization through improving application features, education, and digital literacy.